PENGARUH LINGKUNGAN KERJA FISIK DAN NON FISIK TERHADAP MOTIVASI KERJA DI SEKOLAH DASAR NEGERI SINDUADI TIMUR SLEMAN - Sri Rejeki (JURNAL MANAJEMEN, 2014)
This study was conducted to determine the effect of Work Environment Against Physical and Non-Physical Work Motivation in Elementary School East Sinduadi, Sleman. The type of this research is the nature regresional aimed to see the effect of variable Work Environment Against Physical and Non-Physical Work Motivation variables. As the study variables consist of Work Environment and Physical and Non-Physical Work Motivation variable data were collected using questionnaires and sampling are as many as 25 respondents. accindental sampling. Analysis of data using multiple linear regression. The results using multiple linear regression analysis showed that the results of the multiple linear regression, namely: Y = 2.510 to 0.142 X1 + 0.589 X2 Physical working conditions do not affect the level of motivation of employees working at East Elementary School Sinduadi Sleman value because the test statistic is not significant (0.502 more than 5%). With a negative coefficient (-0.512). Non-physical work environment affects the motivation level of employees working in Sleman East Sinduadi Elementary School because the value of the test statistic showed significant results (0.045 below 5%). Positive coefficient (0.589). Environmental conditions of physical and non-physical work jointly influence the motivation level of employees working at East Elementary School Sinduadi Sleman. It is seen from the value of the test statistic (F) is significant (0.041). With a constant value of 3.615 and a significant level of 5%. Keywords: physical work environment, non-physical work environment, work motivation.